Local adaptation and intraspecific variation of the dominant prairie grass: identifying populations for restoration in future droughts - Sytsma, Jack (My University, 2026)
Understanding how climate, genetic differentiation, and trait variation interact to shape adaptation, abundance, and drought tolerance is critical for predicting ecosystem responses to global change. This dissertation investigates these processes in Andropogon gerardi (big bluestem), a dominant North American tallgrass prairie species, using an integrated approach combining reciprocal garden experiments, ecological genomics, trait-based analyses, and range-wide surveys. The overarching goal was to understand how environmental gradients and genetic variation interact to determine local adaptation, population performance, and resilience under drought. Four complementary objectives guided this research: (1) quantify local adaptation across precipitation gradients; (2) identify molecular and trait-based mechanisms of local adaptation and drought response; (3) evaluate range-wide patterns of abundance, diversity, and trait variation, and (4) assess the relative contributions of genetic differentiation and phenotypic plasticity to intraspecific trait variation (ITV). We hypothesized (1) that local ecotypes would exhibit higher fitness and performance than non-local ecotypes when grown in their home sites (local adaptation) and would be competitively dominant over the surrounding plant community. We expected (2) that drought-adaptive trait assemblages and gene expression profiles will be more pronounced in the dry ecotype compared to the wet ecotype, reflecting genomic and trait-based mechanisms of local adaptation. We hypothesized (3) that population abundance and genetic diversity would peak at the range core, consistent with the Abundant Center Hypothesis (ACH), and trait variation will correspond to linear clines according to climatic gradients, in support of a clinal patterns model (CPM). Finally, we expected (4) that ITV will result primarily from genetic differentiation among populations rather than phenotypic plasticity or short-term environmental acclimation. To test these hypotheses, we first leveraged long-term reciprocal gardens established in 2009 across broad rainfall gradients (500–1200 mm yr⁻¹) and measured cover and biomass of ecotypes and their surrounding plant community. Second, within these gardens, we measured functional traits—including leaf morphology, biomass allocation, phenology, and water-use efficiency among others— and used RNA sequencing to provide transcriptomic data to link gene expression with phenotypic responses. Third, we conducted range-wide measurements of abundance, traits, and genetic diversity across broad environmental gradients in populations spanning sharp temperature (4-21°C, TX-MN USA) and precipitation (350-1400 mm yr⁻¹, CO-NC) gradients. Finally, we used controlled greenhouse experiments to disentangle environmental versus genetic contributions to trait variation of the same populations used in our range-wide demographic study. Our results demonstrate strong local adaptation: A. gerardi ecotypes consistently exhibited higher fitness in home environments with this trend becoming more pronounced at decadal scales. The strength of local adaptation extended to the community level where local ecotypes were competitively dominant over the surround plant community whereas non-local ecotypes allowed for competitive release. Trait-based analyses of ecotypes showed the dry ecotype demonstrated trait assemblages consistent with stress tolerance (increased water-use efficiency, shorter stature) where the wet ecotype showed traits associated with increased light competition (greater height, biomass, and leaf width). At the transcriptome level, differential gene expression revealed drought-responsive genes (e.g., ABA signaling, Drought Induced 19) were upregulated in the dry ecotype, with growth-promoting genes (e.g., Gibberellins, Auxin Response Factors) were upregulated in the wet ecotype. Range-wide analyses showed that abundance and genetic diversity aligned with the ACH, peaking near range centers. In contrast, functional trait variation increased linearly along climatic gradients, supporting the CPM. Finally, ITV was shaped by both climate and underlying genetic differentiation, indicating that precipitation regimes have imposed persistent selective pressures on trait variation. Together, these findings reveal a multi-scalar interplay between environmental selection, evolutionary processes, and functional trait differentiation. This research advances both ecological theory and applied restoration science. Theoretically, it integrates frameworks of local adaptation, ecological genomics, and ITV, providing mechanistic insight into how genotype, phenotype, and environment interact across spatial and temporal scales. Practically, it informs climate-adjusted seed sourcing, ecotype selection, and restoration strategies aimed at enhancing ecosystem resilience under increasing drought and changing rainfall patterns. By combining long-term field experiments, genomic data, and trait-based approaches, this dissertation provides a mechanistic understanding of adaptation in a dominant prairie grass and offers actionable recommendations for land managers. These include identifying drought-tolerant genotypes that can enhance restoration outcomes, such as informing species and genotype selection for large-scale programs such as the Conservation Reserve Program, which manages millions of acres of conservation land.
Keywords: Local adaptation; Ecological genomics; Drought tolerance; Environmental gradients; Intraspecific variation; Functional trait